RANCANG BANGUN GAME PLATFORMER BINTANG KECIL MENGGUNAKAN GODOT ENGINE - Ricky, Ricky; Silalahi, Mesri (LPPM Universitas Putera Batam, 2021)
Entertainment industry comes in many shapes and form. One example of such things are digital video games. Despite the controversies and bad news around it, the industry shows no progress of slowing down. Many people show interest of developing video games, yet the opportunity seems abysmal, at least in this nation. This research paper intended to draw more people to the positive of video game, and possibly encourage them to try develop their own video games. Content of this paper include the basic process of developing a 2D platformer games using Godot Engine. Assets are homemade, meaning the drawing are self-made, with the exception of fonts.